Penerapan Pendidikan Karakter Berbasis Pancasila Pada Mata Pelajaran Budi Pekerti Dan Nasionalisme - Clara Widhani Fauziah; Natasya Karla; Rr.Dinda Bayu Putri; Tasya Maria Agustin Marpaung (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the implementation of character education based on Pancasila values through the local content subject "Budi Pekerti dan Nasionalisme" (BudNas) at SMA 17 Agustus 1945. Employing a qualitative approach, data were collected through in-depth interviews with students and teachers, as well as literature reviews. Data analysis utilized the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The findings indicate that BudNas effectively instills Pancasila values, such as tolerance, mutual cooperation, and patriotism. However, limited teaching hours and monotonous teaching methods remain significant challenges. Recommendations include extending lesson duration, adopting more interactive methods, and engaging students in practical activities to optimize learning outcomes.